2008
DOI: 10.1176/appi.ap.32.6.484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Evidence-Based Tobacco Treatment Curriculum for Psychiatry Residency Training Programs

Abstract: Objective-Smokers with mental illness and addictive disorders account for nearly one in two cigarettes sold in the United States and are at high risk for smoking-related deaths and disability. Psychiatry residency programs provide a unique arena for disseminating tobacco treatment guidelines, influencing professional norms, and increasing access to tobacco cessation services among smokers with mental illness. The current study evaluated the Rx for Change in Psychiatry curriculum, developed for psychiatry resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…Psychiatric inpatient settings that have voluntarily adopted smoke-free policies have done so with little to no disruption in clinical care (Lawn & Pols, 2005). Incorporating evidence-based tobacco treatment curriculum in psychiatry and psychology residency training programs would provide increased delivery of cessation interventions for smokers with mental illness because it has been shown to improve residents' knowledge, attitudes, confidence, and behaviors for treating tobacco dependence among patients with mental illness (Prochaska, Fromont, et al, 2008). Also, enhancing quitline counseling protocols to best meet the needs of smokers with mental illness would provide an opportunity to improve successful quitting among this group as a recent study indicated that about 25% of smokers who called a large state quitline had major depression in the past two weeks, and they had lower successful quit rates than nondepressed smokers (Hebert, Cummins, Hernández, Tedeschi, & Zhu, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric inpatient settings that have voluntarily adopted smoke-free policies have done so with little to no disruption in clinical care (Lawn & Pols, 2005). Incorporating evidence-based tobacco treatment curriculum in psychiatry and psychology residency training programs would provide increased delivery of cessation interventions for smokers with mental illness because it has been shown to improve residents' knowledge, attitudes, confidence, and behaviors for treating tobacco dependence among patients with mental illness (Prochaska, Fromont, et al, 2008). Also, enhancing quitline counseling protocols to best meet the needs of smokers with mental illness would provide an opportunity to improve successful quitting among this group as a recent study indicated that about 25% of smokers who called a large state quitline had major depression in the past two weeks, and they had lower successful quit rates than nondepressed smokers (Hebert, Cummins, Hernández, Tedeschi, & Zhu, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Published literature, however, suggested that health care professionals who receive training for tobacco cessation counseling demonstrated increased delivery of tobacco cessation interventions, 28 and a 4-hour training of the Rx for Change program for psychiatry medical residents resulted in measureable changes in self-reported tobacco cessation counseling behavior, validated through chart reviews. 29 Increased training for health care professionals on tobacco cessation will be pivotal to address the number of patients needing this service, which emphasizes the need to reduce barriers to inclusion of tobacco cessation training in required coursework. Sixty-eight percent of pharmacy faculty have identified lack of available curriculum time as a very or extremely important barrier to enhanced tobacco education.…”
Section: Discussionmentioning
confidence: 99%
“…The teaching strategies include reading materials for students, slides with instructor notes, videos of trigger scenarios, case scenarios for role playing and counseling sessions. The program is usually implemented in 6-8 h and has been shown to be effective in improving students' perceived abilities and confidence in providing tobacco cessation counseling to patients [21] and improving psychiatry residents' cessation counseling behaviors [22] .…”
Section: The Teaching Modulementioning
confidence: 99%